Factors associated with leprosy in children contacts of notified adults in an endemic region of Midwest Brazil - Thaísa S.V. Rodrigues; Luciane C. Gomes; Denise C.B. Cortela; Eliane A. Silva; Cristiane A.L. Silva; Silvana M.B. Ferreira (Brazilian Society of Pediatrics, 2020)
Objectives: To analyze the factors associated with leprosy in children who were intradomiciliary contacts of notified adults with the disease in an endemic municipality in Mato Grosso, Brazil. Method: Case-control study with 204 children under 15 years of age, living in an endemic municipality. Cases (n = 40) were considered as the children with leprosy registered at the National Information System of Notifiable Diseases in 2014 and 2015, who were intradomiciliary contacts of at least one adult diagnosed with the disease in the family, and as a control group (n = 164) of children living within a radius of up to 100 m of the notified cases. Data were obtained through medical file analysis, interviews, and blood samples for anti‐PGL‐I serological test by the ELISA method. The binary logistic regression technique was used, with p ≤ 0.05. Results: After adjustments, the following were associated with leprosy: age (95% CI: 1.24-9.39, p = 0.018), area of residence (95% CI: 1.11-6.09, p = 0.027), waste disposal (95% CI: 1.91-27.98, p = 0.004), family history of the disease (95% CI: 3.41-22.50, p = 0.000), and time of residence (95% CI: 1.45-7.78, p = 0.005). Conclusion: Factors associated with the disease indicate greater vulnerability of children aged 8-14 years, associated with living conditions and time of residence, as well as the family history of the disease. Resumo: Objetivos: Analisar os fatores associados à hanseníase em crianças contatos intradomiciliares de adultos notificados com a doença em município endêmico, Mato Grosso, Brasil. Método: Estudo caso‐controle com 204 menores de 15 anos residentes em um município endêmico. Consideraram‐se casos (n = 40) crianças registradas com hanseníase no Sistema Nacional de Agravos de Notificação em 2014 e 2015 e que eram contatos intradomiciliares de pelo menos um adulto diagnosticado com a doença na família e como grupo controle (n = 164) crianças residentes a um raio de 100 metros dos casos notificados. Os dados foram obtidos por meio de análise de prontuários, entrevistas e coleta de amostras de sangue para investigação sorológica do anti‐PGL‐I pelo método Elisa. Usou‐se a técnica de regressão logística binária e p ≤ 0,05. Resultados: Mostraram‐se associados à hanseníase após ajustes: idade (IC 95%: 1,24-9,39; p = 0,018), zona de residência (IC 95%: 1,11‐6,09; p = 0,027), destino de lixo (IC 95%: 1,91‐27,98; p = 0,004), história da doença na família (IC 95%: 3,41‐22,50; p = 0,000) e tempo de moradia (IC 95%: 1,45‐7,78; p = 0,005). Conclusão: Os fatores associados à doença indicam maior vulnerabilidade em menores de 8 a 14 anos, ligadas as condições e ao tempo de moradia, bem como a história da doença na família.